Antibiotic Stewardship: Perception of General Practitioners regarding Emerging Challenges - Tabinda Ashfaq, Fauzia Akhter, Aiesha Faisal, Kashif Ali Samin, Fahad Saleem (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Antibiotics are among the most frequently prescribed classes of drugs all over the world with approximately 50% of it being used without any rationale. This leads to increase antibiotic resistance and further complications. General practitioners are first line of contact and majority of the general population presents them for their health issues. Their perception and attitude regarding antibiotic prescription plays an important role in emerging antibiotic resistance. Objective: To identify knowledge and perception of General practitioners regarding antibiotic stewardship and associated challenges Methodology: This is a cross-sectional study conducted through online platform conducted through a pretested self-administered questionnaire. It included questions related to location and workplace information. Knowledge and practices of the participants regarding antibiotic use in their clinical practice and experience of health care workers related to patient exposure and protective equipment. Data was entered and analyzed using SPSS statistical software Version 19. Results: A total of 270 out of 373 agreed to participate in the study with a response rate of 72%. On exploring relevance of importance of antibiotic resistance in daily work majority 81% agreed that it is highly relevant. Similarly, when asked about reasons for increasing antibiotic irrational use of antibiotics was a major reason identified by 96% of male and 84% of females. Physicians play a very significant role in education of patients regarding antibiotic resistance when prescribing medicine. To explore GPs practice regarding education to patients around 66% of male and 85% of the females agreed that they educate their patients when prescribing while 35 % male and 15% female physicians did not educate their patients because of lack of time available for patient education during consultation. Conclusion: Antibiotic resistance is on the rise. General practitioners have limited knowledge regarding rationale use, however their practice is limited due to poor accountability, increase demand from patients and to enhance their patient satisfaction Keywords: Antibiotics, stewardship, general practitioners.